2009
DOI: 10.1055/s-0028-1115324
|View full text |Cite
|
Sign up to set email alerts
|

Giant-Cell Tumors of the Temporal Bone: Management Strategies

Abstract: Objective: To discuss the current management options for giant-cell tumors (GCTs) involving the temporal bone and present two case reports and a review of the literature. Method: In a tertiary-care academic medical center, two patients with GCTs of the temporal bone were evaluated and managed. The patients underwent gross total resection and curettage of GCTs involving the temporal bone. Afterward, both patients were evaluated for postoperative complications as well as for recurrence. Results: Two patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…Around 1-2% of these lesions present in the head and neck [Cook et al, 1986;Lee and Lum, 1999;Gibbons et al, 2000;Leonard et al, 2001;Isaacson et al, 2009], with the skull base being a commonly reported site (temporal, sphenoid and ethmoid bones) and other sites including the mandible, maxilla, nasal cavity, thyroid, larynx, hyoid, tongue and the soft tissues of the neck. In the skull base the temporal bone is a common site of occurrence of GCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Around 1-2% of these lesions present in the head and neck [Cook et al, 1986;Lee and Lum, 1999;Gibbons et al, 2000;Leonard et al, 2001;Isaacson et al, 2009], with the skull base being a commonly reported site (temporal, sphenoid and ethmoid bones) and other sites including the mandible, maxilla, nasal cavity, thyroid, larynx, hyoid, tongue and the soft tissues of the neck. In the skull base the temporal bone is a common site of occurrence of GCTs.…”
Section: Introductionmentioning
confidence: 99%
“…MGCs of extracranial GCT and GCG are immunohistologically positive for CD 68, and shows histiocytic differentiation [6]. We also detected CD68 positive cells in the presented case, and P63 immunostaining may use differentiating GCTs from GCGs, and it is positive in GCT [7]. Negative P63 immunostaining indicated that the cells were not of epithelial origin.…”
Section: Disclosurementioning
confidence: 56%
“…The GCGs appear as an osteolytic lesion on skull radiography and has marginal sclerosis on CT [7]. Nackos, et al [8] published CT findings of 7 cases GCG, in which all 7 cases showed mixed density, and enhanced heterogeneously.…”
Section: Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…CT demonstrates an advantage in revealing the extent of disease, particularly in the bone cortex. The differences between D-GCTS and osteosarcoma or chondrosarcoma may be determined from the CT results (17,21), as diffuse thickening of soft tissues around the joints, oppressive absorption of the affected bones, the presence of a clear boundary, the lack of periosteal reaction and the presence of a soft tissue mass also without calcification or ossification may be observed on CT (13,21,22). MRI has an extremely high sensitivity and specificity for the diagnosis of G-GCTS (16,23).…”
Section: Discussionmentioning
confidence: 99%